Digital skills for managing a digital environment: the case of e government delivery in Namibia - Dias, Henda Pombili (My University, 2021)
Despite efforts to implement e-government in Namibia, there is limited progress in availing online services, interactive websites, and related initiatives. This study explored the digital skills that are required by management for the effective implementation of e-government interventions. Specifically, it identified the required digital skills and examined how emerging technologies and the characteristics of the digital environment influence these skills. The study also investigated varying approaches to the process of developing digital skills. The research adopted a case study approach focusing on the progress of e-government implementation in Namibia. Responses were drawn from respondents directly involved in the implementation of e-government. The findings indicate a consensus that digital skills are required in e-government and also revealed a gap between the understanding of digital skills and the awareness of how the characteristics of the digital environment shape digital skills. The findings also indicated the need for appropriate measures to address the limited availability of these skills. The study concluded that the concept of digital skills is still evolving and has various defining implications. Furthermore, there are divergent viewpoints about the availability of digital skills that are required to implement e-government. The study informs decisions that minimise obstacles to the acquisition of digital skills and shares innovative approaches to developing the skills required to implement e-government initiatives. It further contributed to the formulation of relevant policies, best practices, and strategies for digital skills undertakings
A research project submitted in partial fulfilment of the requirements for the degree Master of Arts in the field of ICT Policy and Regulation to the Faculty of Humanities, University of the Witwatersrand, 2021